Delayed type hypersensitivity reactions to various allergens may differently model inflammatory skin diseases. Issue 1 (8th October 2022) - Pavel, Ana B.; Del Duca, Ester; Cheng, Julia; Wu, Jianni; Ungar, Benjamin; Estrada, Yeriel D.; Jack, Carolyn; Maari, Catherine; Proulx, Étienne Saint‐Cyr; Ramirez‐Valle, Francisco; Krueger, James G.; Bissonnette, Robert; et al.
Abstract: Background: Treatment of inflammatory skin diseases, including atopic dermatitis (AD) and psoriasis, is undergoing transformative changes, highlighting the need to develop experimental models of skin inflammation in humans to predict treatment responses. Methods: We topically or intradermally administered four common sensitizers (dust mite (DM), diphencyprone (DPCP), nickel (Ni), and purified protein derivative (PPD)) to the backs of 40 healthy patients and the skin hypersensitivity response was biopsied and evaluated using immunohistochemistry, RNA‐seq, and RT‐PCR. Results: All agents induced strong increases in cellular infiltrates (T‐cells and dendritic cells) as compared to untreated skin ( p < .05), with variable T helper polarization. Overall, DPCP induced the strongest immune responses across all pathways, including innate immunity (IL‐1α, IL‐8), Th1 (IFNγ, CXCL10), Th2 (IL‐5, CCL11), and Th17 (CAMP/LL37) products, as well as the highest regulatory tone (FOXP3, IL‐34, IL‐37) (FDR <0.01). Nickel induced Th17 (IL‐17A), Th1 (CXCL10) and Th2 (IL‐4R) immune responses to a lesser extent than DPCP ( p < .05). PPD induced predominantly Th1 (IFNγ, CXCL10, STAT1) and Th17 inflammation (IL‐17A) ( p < .05). DM induced modulation of Th2 (IL‐13, CCL17, CCL18), Th22 (IL‐22), and Th17/Th22 (S100A7/9/12) pathways ( p < .05). Barrier defects that characterize both AD and psoriasis were best modeled by DPCP and Ni, followed by PPD, including downregulation of terminal differentiation (FLG, FLG2, LOR, LCEs), tight junction (CLDN1/CLDN8), and lipid metabolism (FA2H, FABP7)‐related markers. Conclusion: Our data imply that DPCP induced the strongest immune response across all pathways, and barrier defects characteristic of AD and psoriasis. Abstract : Diphencyprone induced the strongest immune responses across all pathways and modeled barrier defects characteristic of AD and psoriasis. Ni induced all immune pathways at a lesser extent than DPCP. PPD induced predominantly Th1 and Th17, while DM induced predominantly Th2 and Th17/Th22 inflammation.Abbreviations: AD, atopic dermatitis; CAMP, cathelicidin antimicrobial peptide; CCL, C‐C chemokine ligand; CXCL, C‐X‐C motif chemokine; DM, dust mite; DPCP, diphencyprone; IFN, interferon; IL, interleukin; Ni, nickel; PCR, polymerase chain reaction; PPD, purified protein derivative; S100A, S100 calcium binding protein A; STAT1, signal transducer and activator of transcription 1 ; Th, T helper